Effects of Oxidative Stress on Airway Epithelium Permeability in Asthma and Potential Implications for Patients with Comorbid Obesity - Kim HR; Ingram JL; Que LG (Journal of Asthma and Allergy, 2023)
Haein R Kim, Jennifer L Ingram, Loretta G Que Division of Pulmonary, Allergy, and Critical Care Medicine, Duke University Medical Center, Durham, NC, USACorrespondence: Haein R Kim, Division of Pulmonary, Allergy and Critical Care Medicine, Duke University Medical Center, Durham, NC, USA, Tel +1 7063722118, Email hk234@duke.eduAbstract: 20 million adults and 4.2 million children in the United States have asthma, a disease resulting in inflammation and airway obstruction in response to various factors, including allergens and pollutants and nonallergic triggers. Obesity, another highly prevalent disease in the US, is a major risk factor for asthma and a significant cause of oxidative stress throughout the body. People with asthma and comorbid obesity are susceptible to developing severe asthma that cannot be sufficiently controlled with current treatments. More research is needed to understand how asthma pathobiology is affected when the patient has comorbid obesity. Because the airway epithelium directly interacts with the outside environment and interacts closely with the immune system, understanding how the airway epithelium of patients with asthma and comorbid obesity is altered compared to that of lean asthma patients will be crucial for developing more effective treatments. In this review, we discuss how oxidative stress plays a role in two chronic inflammatory diseases, obesity and asthma, and propose a mechanism for how these conditions may compromise the airway epithelium.Keywords: asthma, epithelium permeability, obesity, oxidative stress